Accessibility on a Finnish city government website - Karasti, Juho (My University, 2023)
Accessibility is an important, but often overlooked topic on the web that is slowly gaining importance in societies around the world as it allows people with a wide range of disabilities to use public services, and it also makes them much more usable for all people. State governments and other international institutions have taken notice of improving accessibility on the various websites and other digital services they provide, but what does this entail for a city government website in Finland? This thesis aims to find an answer through four research questions. First, what guidelines should be taken into account and where these requirements come from? Second, how should these guidelines be taken into consideration when designing and developing a website? The analytical part of the thesis continues by exploring how the successful implementation of the guidelines could be measured and analysed. And, finally, an accessibility evaluation is carried out on both the old and the new website of the city of Pori, a medium size city located on the west coast of Finland to evaluate how well the required guidelines are followed on its newly built website. The first three research questions are answered through available literature and legal resources, where as the last one is answered through an accessibility evaluation carried out on the website of the city of Pori. Although the design and content on the city of Pori website is unique to it, the challenges and solutions discussed in this thesis are general enough that they could potentially support future efforts to implement accessibility on the web.
Keywords: accessibility, web, government, website